A preliminary study of SF6 based inductively coupled plasma etching techniques for beta gallium trioxide thin film. (November 2015) - Liang, Hongwei; Chen, Yuanpeng; Xia, Xiaochuan; Zhang, Chao; Shen, Rensheng; Liu, Yang; Luo, Yingmin; Du, Guotong
Abstract: Beta phase Gallium trioxide ( β -Ga2 O3 ) thin film was grown by metal organic chemical vapor deposition technology. Mixture gases of SF6 and Ar were used for dry etching of β -Ga2 O3 thin film by inductively coupled plasma (ICP). The effect of SF6 /Ar (etching gas) ratio on etch rate and film etching damage was studied. The etching rate and surface roughness were measured using F20-UN thin film analyzer and atomic force microscopy showing that the etching rate in the range between 30 nm/min and 35 nm/min with an improved surface roughness was obtained when the reactive mixed gas of SF6 /Ar was used. The analysis of X-ray diffraction and transmission spectra further confirmed the non-destructive crystal quality. This work demonstrates that the properly proportioned mixture gases of SF6 /Ar is suitable for the dry etching of β -Ga2 O3 thin film by ICP and can serve as a guide for future β -Ga2 O3 device processing.